Prevalence, antibiotic resistance and biofilm formation of Salmonella in raw chicken meats at selected slaughterhouses in Peninsular Malaysia - Ismail, Zuraidah (2019)
Salmonella is one of the most common causes of foodborne diseases. The objectives of this research were to isolate and identify Salmonella from raw chicken meat, determine its antibiotic resistance and its ability to form biofilm on the surfaces using microtitre plate surface in a growth media at different incubation period. Raw chicken meat was obtained from selected slaughterhouses located in four different zones in Peninsular Malaysia; Northern Zone (States of Perlis, Kedah, Penang and Perak); Central Zone (States of Selangor, Negeri Sembilan and Melaka; Southern Zone (States of Johor) and Eastern Zone (States of Terengganu, Kelantan and Pahang). The samples were collected and isolated at the Veterinary Public Health Laboratory (VPHL), Department of Veterinary Services (DVS), Sepang, Selangor. Isolation and identification of samples were performed using an in-house conventional (VPHL) culture method adopted from the American Association of Analytical Chemists (AOAC, 1995), the Food Safety and Inspection Services of USDA (FSIS, 1998) and the Australian Standard (AS 1766.2.5, 1991). Positive isolates were serotyped at the Veterinary Research Institute, Ipoh Perak using the White-Kauffmann-Le Minor scheme comprising of commercial somatic and flagellar antisera. The antibiotic resistance of 135 Salmonella isolates was investigated via the Kirby-Bauer disk-diffusion method, using 12 antibiotics. The biofilm-forming ability of the isolates was assessed using two media; a tryptic soy broth (TSB) and a 1/20 TSB with incubation periods of 24 and 48 hours at 37 °C. Crystal violet staining was used for the quantification of Salmonella isolates based on the difference between optical density measurements of the test and negative control samples (ΔOD590nm). It was found that 17.31% (135/780) of the raw chicken meat tested positive for Salmonella. Serotyping of the total 135 isolates demonstrated that 87 (64.44%) belonged to 12 different serovars; S. Corvallis, S. Brancester, S. Enteritidis, S. Albany, S. Typhimurium, S. Braenderup, S. Hindmarsh, S. Hiddudify, S. Bellevue, S. Duesseldorf, S. Cyprus and S. Indiana. The results showed that the Salmonella isolates had the highest percentage of resistance to erythromycin (87.41%) and tetracycline (85.19%). Salmonella isolates were also resistant to sulphamethoxazole/trimethoprim (55.55%), ampicillin (26.63%), streptomycin (29.63%), enrofloxacin (22.96%) and nalidixic acid (17.04%). In contrast, lower percentage of resistance was observed against gentamicin (7.41%), cephalothin (5.96%), ceftriaxone (3.70%) and amoxicillin-clavulanic acid (2.22%). All Salmonella isolates were susceptible to ciprofloxacin (CIP). The multiple antibiotic resistance (MAR) index varied from 0.08 to 0.75. A total of 93 isolates (68.88%, 93/135) were multi-drug resistant. Meanwhile, more than 85% of 135 Salmonella isolates were able to form biofilm in TSB and 1/20-TSB media. A greater quantity of Salmonella were able to produce biofilm 1/20-TSB (90.37%) compared to TSB (88.15%), respectively. The maximum biofilm (94.81%) formed by Salmonella isolates was at 24 hours incubation in 1/20-TSB whereas 88.89% biofilm formed in TSB. The occurrence and antibiotic resistance profiles of Salmonella isolates in slaughterhouses could promote awareness on controlling Salmonella at all production stages of raw chicken meat in Peninsular Malaysia. The ability of Salmonella to form biofilm could indicate common factors promote biofilm formation; thus further work could develop interventions to reduce this incidence.